“My motivation is to pursue what it means to be free today”: a conversation with Marcelo Cidade - Scovino, Felipe; Cidade, Marcelo (PORTO ARTE: Revista de Artes Visuais, 2018)
In an interview with Felipe Scovino, artist Marcelo Cidade revisits different works he made in the 2000s and 2010s, pointing out his motivations and commenting on the critical dimensions of that work, usually focused on public space, either as a field of action or as theme. Themes like the relations between art and crime emerge in the conversation, ranging from issues related to fear, social surveillance, institutionalized violence and the exercise of freedom. The interview also discusses the dialogue between contemporary art production and the historical and historiographic tradition of art.